2009
DOI: 10.1007/s11101-009-9134-8
|View full text |Cite
|
Sign up to set email alerts
|

Terminalia arjuna a sacred medicinal plant: phytochemical and pharmacological profile

Abstract: Terminalia arjuna Wight & Arn. (Combretaceae) is a tree having an extensive medicinal potential. The plant is used traditionally in the treatment of various aliments. T. arjuna is a very good hypocholsteremic, hypolipidemic, anticoagulant, antihypertensive, antithrombotic, antiviral, antifungal and antibacterial agent Various parts of plant have been investigated for the presence of phytoconstituents and pharmacological activities. Many useful phytoconstituents have been isolated from T. arjuna. Triterpenoids … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
46
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(47 citation statements)
references
References 30 publications
(21 reference statements)
0
46
0
Order By: Relevance
“…Fruits and Bark of T. arjuna have been used as diuretic [1], tonic [4] an antioxidant [5], anticancer [6,7] hypocholesterolaemic, hypolipidemic [8][9][10], antiulcer [11], antiviral, antifungal and antibacterial [12][13][14][15][16] agents. A number of triterpenoids, saponines, tannins, cardenolides and flavonoids were reported from earlier phytochemical investigations of T. arjuna [17][18][19][20][21][22][23][24]. In the present study, we have isolated one xanthone identified as 2,7-dimethoxyxanthone (1) [ Fig.…”
Section: Introductionmentioning
confidence: 55%
“…Fruits and Bark of T. arjuna have been used as diuretic [1], tonic [4] an antioxidant [5], anticancer [6,7] hypocholesterolaemic, hypolipidemic [8][9][10], antiulcer [11], antiviral, antifungal and antibacterial [12][13][14][15][16] agents. A number of triterpenoids, saponines, tannins, cardenolides and flavonoids were reported from earlier phytochemical investigations of T. arjuna [17][18][19][20][21][22][23][24]. In the present study, we have isolated one xanthone identified as 2,7-dimethoxyxanthone (1) [ Fig.…”
Section: Introductionmentioning
confidence: 55%
“…In fact, a number of pharmacological studies have validated the ethnomedical reputation of the bark of T. arjuna as an excellent cardiotonic agent [6] . Among the various kinds of secondary metabolites isolated from this plant, the triterpenoids and glycosides were shown to be particularly effective in treatment of cardiovascular diseases, while the flavonoids and polyphenols exerted antioxidant, hypolipidemic, and antiinflammatory properties [5,18] . So far, the antimicrobial potential of T. arjuna have been sparsely investigated against only a few selected bacterial and fungal species [7,8] .…”
Section: Discussionmentioning
confidence: 99%
“…MIC for TAM and TAW against the fungal isolates was determined in a similar procedure, using sabouraud dextrose broth in 96-well microtitre plates incubated for 18 h at 35 °C [13,14] . The presence of visible growth was determined spectrophotometrically as above.…”
Section: Fungal Strainsmentioning
confidence: 99%
“…There are, however, other medicinal applications of T. arjuna bark extracts such as its being an astringent, aphrodisiac, tonic, or used in therapy of fractures, ulcers, diabetes, tumors, inflammation, skin disorders (Kumar 2014;Paarakh 2010). Some of these activities have already been experimentally approved, e.g., antioxidant and anticancer action (Jain et al 2009), or anti-inflammatory, imunomodulatory, and antinociceptive action (Halder et al 2009). The effect of this plant on cough and respiratory system has not yet been investigated.…”
Section: Introductionmentioning
confidence: 99%